2022
DOI: 10.3847/1538-4357/ac5d3a
|View full text |Cite
|
Sign up to set email alerts
|

Quenching and the UVJ Diagram in the SIMBA Cosmological Simulation

Abstract: Over the past decade, rest-frame color–color diagrams have become popular tools for selecting quiescent galaxies at high redshift, breaking the color degeneracy between quiescent and dust-reddened star-forming galaxies. In this work, we study one such color–color selection tool—the rest-frame U − V versus V − J diagram—by employing mock observations of cosmological galaxy formation simulations. In particular, we conduct numerical experiments assessing both trends in galaxy properties in UVJ space and the color… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 137 publications
(238 reference statements)
1
7
0
Order By: Relevance
“…It may still be possible to catch a quiescent galaxy in its dusty phase if the quenching timescale is longer than the gas depletion timescale. A few galaxies with some measure of dust obscuration (verified via Atacama Large Millimeter/submillimeter Array detections) have been reported in the literature (Schreiber et al 2018;Whitaker et al 2021b) and found in simulations (Akins et al 2022). While it is possible that these galaxies may indeed represent an evolutionary phase for quiescent galaxies, it is equally likely that they are dusty star-forming galaxies masquerading as quiescent galaxies due to their low sSFRs (heavily dependent on the choice of SFH, e.g., Marchesini et al 2010).…”
Section: Possible Limitations Of the (Ugi) S Diagrammentioning
confidence: 91%
“…It may still be possible to catch a quiescent galaxy in its dusty phase if the quenching timescale is longer than the gas depletion timescale. A few galaxies with some measure of dust obscuration (verified via Atacama Large Millimeter/submillimeter Array detections) have been reported in the literature (Schreiber et al 2018;Whitaker et al 2021b) and found in simulations (Akins et al 2022). While it is possible that these galaxies may indeed represent an evolutionary phase for quiescent galaxies, it is equally likely that they are dusty star-forming galaxies masquerading as quiescent galaxies due to their low sSFRs (heavily dependent on the choice of SFH, e.g., Marchesini et al 2010).…”
Section: Possible Limitations Of the (Ugi) S Diagrammentioning
confidence: 91%
“…The UVJ diagram (or other similar rest-frame color-color selections; e.g., Arnouts et al 2013;Leja et al 2019;Antwi-Danso et al 2022) has become ubiquitous to distinguish between star-forming and quiescent galaxies (Brammer et al 2009;Williams et al 2009;Whitaker et al 2011;Ilbert et al 2013;Muzzin et al 2013;Davidzon et al 2017;Akins et al 2022). While rest-frame color selections have been used when studying integrated galaxy properties, the comparably worse sensitivity and spatial resolution of Spitzer/IRAC (i.e., the only instrument able to image the rest-frame J band at z  1) has limited resolved studies of high-redshift galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Although the differences are slight, the implications of the lack of overlap in parameter space are potentially significant. For instance, several uncertainties in the forward modeling of the Cosmic Sands galaxies exist, including the stellar population modeling (the IMF, stellar isochrones, and the stellar spectral library chosen to model the luminosity of the star particles; see, e.g., Akins et al 2022), the handling of unresolved emission from H II and photodissociation regions in the birth-clouds surrounding young stars, and the assumed optical properties of the dust grains and thus the underlying extinction curve of the galaxy spectrum. Modifying the optical properties of the dust grains would propagate changes in the resulting infrared luminosity for the same dust and stellar mass values.…”
Section: Dust Properties and Infrared Luminositiesmentioning
confidence: 99%